Climate change and the Madden‐Julian Oscillation: A vertically resolved weak temperature gradient analysis - Brandon O. Wolding; Eric D. Maloney; Stephanie Henderson; Mark Branson (Journal of Advances in Modeling Earth Systems, 2017)
Abstract WTG balance is used to examine how changes in the moist thermodynamic structure of the tropics affect the MJO in two simulations of the Superparameterized Community Earth System Model (SP‐CESM), one at preindustrial (PI) levels of CO2 and one where CO2 levels have been quadrupled (4×CO2). While MJO convective variability increases considerably in the 4×CO2 simulation, the dynamical response to this convective variability decreases. Increased MJO convective variability is shown to be a robust response to the steepening vertical moisture gradient, consistent with the findings of previous studies. The steepened vertical moisture gradient allows MJO convective heating to drive stronger variations in large‐scale vertical moisture advection, supporting destabilization of the MJO. The decreased dynamical response to MJO convective variability is shown to be a consequence of increased static stability, which allows weaker variations in large‐scale vertical velocity to produce sufficient adiabatic cooling to balance variations in MJO convective heating. This weakened dynamical response results in a considerable reduction of the MJO's ability to influence the extratropics, which is closely tied to the strength of its associated divergence. A composite lifecycle of the MJO was used to show that northern hemisphere extratropical 525 hPa geopotential height anomalies decreased by 27% in the 4×CO2 simulation, despite a 22% increase in tropical convective heating associated with the MJO. Results of this study suggest that while MJO convective variability may increase in a warming climate, the MJO's role in “bridging weather and climate” in the extratropics may not.